Auditing and assurance services an integrated approach - Arens, Alvin A.
"Includes coverage of international standards and global auditing issues, in addition to coverage of PCAOB Auditing Standards, the risk assessment SASs, the Sarbanes/Oxley Act, and Section 404 audits."